Old People as Traffic Special Participants - Susło, Robert; Siuta, Jędrzej; Trnka, Jakub; Gęsicki, Marcin; Drobnik, Jarosław (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Books and papers have been reviewed to find out which changes typical for old people are influencing the way they are taking part in traffic and results of the autopsies performed in the Forensic Medicine Department, Medical University, Wroclaw, Poland in the years 2008–2009 have been analyzed to choose the cases of people of the age 60 years and above, that died because of traffic accidents. Old people constitute a special group of traffic participants, because with ageing processes in the human organism and resulting organ changes, there is an increased risk of incurring injuries or dying because of traffic accidents, the complications of the trauma related to traffic accidents are more common and grave. They do not take into account the psychophysical fitness limitations connected with the age and often play also the very demanding role of the drivers and bikers. It is also depictured in the analyzed autopsy results. The results of the study suggest the need to consider a possibility of introducing in Poland a periodic verification of older people abilities to drive vehicles in public roads.